1968
DOI: 10.1149/1.2410847
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Adenine: Reaction Products and Mechanisms

Abstract: The electrochemical oxidation of adenine (6‐aminopurine), which gives a single well‐defined voltammetric wave at the pyrolytic graphite electrode (PGE), was investigated by macroscale controlled electrode potential at the PGE in aqueous 1M acetic acid solution (pH 2.3) with exhaustive isolation, identification, and determination of reaction products and intermediates. The electrochemical oxidation of adenine appears to follow initially the same path as the enzymatic oxidation, but further oxidation and fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
1

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 25 publications
4
92
0
1
Order By: Relevance
“…This result suggested that Fenton-generated hydroxyl radicals induced oxidative damage on adenine bases fol-lowing a pathway somehow different from the electrochemical oxidation because the adsorbed compound was not formed or the yield was so low that cannot be detected by CV. At this point it is important to remark that the NADH catalyst generated on the electrode surface after oxidation of adenine residues is not the main oxidation product but only one of the several electrogener-ated products reported so far (Dryhurst and Elving, 1968;Goyal et al, 1991;Goyal and Sangal, 2002).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This result suggested that Fenton-generated hydroxyl radicals induced oxidative damage on adenine bases fol-lowing a pathway somehow different from the electrochemical oxidation because the adsorbed compound was not formed or the yield was so low that cannot be detected by CV. At this point it is important to remark that the NADH catalyst generated on the electrode surface after oxidation of adenine residues is not the main oxidation product but only one of the several electrogener-ated products reported so far (Dryhurst and Elving, 1968;Goyal et al, 1991;Goyal and Sangal, 2002).…”
Section: Resultsmentioning
confidence: 91%
“…Ascorbic acid is a potent reductant agent that can reduce metal transition ions, thus, a potential pro-oxidant role in vivo was suggested (Podmore et al, 1998). However, most evidences point out to a predominant antioxidant role of ascorbic acid (Carr and Frei, 1999;Evans and Halliwell, 2001). Owing to the fact that DPV is a technique more sensitive than CV, it was used for calibra-tion purposes.…”
Section: Determination Of Antioxidant Capacitymentioning
confidence: 99%
“…Adenine oxidation is also irreversible, and occurs in three steps [5,6]; and for millimolar concentrations, these peaks could be identified by fast cyclic voltammetry, 3 V s À 1 [6]. However, the sharper adenine oxidation peak found at 1-mM concentrations splits into two peaks for 10 mM and another electrode processes was identified by differential pulse voltammetry, Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The potential at which the oxidation of DNA bases occurs depends on the pH of the electrolyte buffer solution, since the potentials for purine base oxidation follow a 60 mV per pH unit dependence [13]. Therefore, the higher the pH of the electrolyte buffered solution, the less positive is the potential necessary for guanosine or adenosine oxidation and the same is valid for their corresponding nucleotides.…”
Section: Voltammetry Of Polyadenosine Odn Lipoplexesmentioning
confidence: 99%